TEKNOLOGI HYBRID PANAS MATAHARI DAN LISTRIK PADA MESIN PENETAS TELUR OTOMATIS BERBASIS MIKROKONTROLER AVR ATMEGA8535 - Titi Andriani; Muhammad Hidayatullah; Shinta Esabella (Hexagon Jurnal Teknik dan Sains, 2020)
An Egg hatching matchine using hybrid technology which is a combination of solar heat and electrical energy is designed to utilize solar thermal energy so as to reduce the amount of electricity used. The design of this egg incubator includes (1) general system design which includes LM35 temperature sensor, SHT11 temperature and humidity sensor, several lamps and fans, and lyquid crystal dysplay; (2) mechanical design includes the design of electrical installations and wire mesh placed in such a way in a rectangular and glass-enclosed container; and (3) software design includes programs that are used to control the system. From the test results during the process from the beginning to the end of the test it turns out that the condition of the equipment is still normal and there are no significant disturbances, so that the egg incubator is ready to be applied in automatic hatching that is as expected.